PENGEMBANGAN APLIKASI SISTEM E-TICKETING KONSER MUSIK DENGAN SEATING NUMBER PADA WEBSITE MOTIKDONG.COM - Wahyudi Wahyudi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
E-Ticketing is a way to document the online sales process that results in the form of tickets that can make it easier for people to buy tickets for events, all concerts from the website. Tickets can be purchased online through payment using the transfer method or credit card. Customers no longer need to spend time for coming to buy ticket on location, they can directly order concert tickets that are sold from anywhere and at any time with the ease of various means of payment, and do not have to worry about lost tickets, stolen, left behind, or even splashed with water. E-ticketing even allows you to buy tickets for relatives and others. The problem is that customers still need to exchange physical tickets and choose the seats they will occupy when watching a concert, so they have to be present early if they want to get the seats that they want, because if they are present later it will cause the selected seats to be occupied by others. In this case the author will try to develop a concert ticket sales information system with a seating number method. The results of this study are expected to be able to overcome the above problems, so that customers can immediately choose a seat when ordering concert tickets on the website.